STRIFE FOR POWER IN RON HOWARD'S ANGEL AND DEMON MOVIE (2009): A MARXIST APPROACH - LISTYONINGRUM, DEWI (2011)
The subject of the study is Angel and Demon movie by Ron Howard. This study is aimed to show strife for power by Robert Langdon in Angel and Demon movie by using Marxist approach. The objective of the study is to analyze the structural elements and to analyze the movie based on Marxist approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the Angel and Demon movie directed by Ron Howard released in 2009. While the secondary data sources are other materials taken from books, journal, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, mise-en-scene, cinematography, sound and editing are related to each other and form the unity into good quality of a movie. Second, based on the Marxist analysis, there is close relation between the movie production and the underlying social reality which reflected the strife for power.